2011
DOI: 10.1590/s0100-69162011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal modelling of the duration of the cotton cycle in the State Of Goiás, Brazil

Abstract: The objective of this work was to develop and validate a mathematical model to estimate the duration of cotton (Gossypium hirsutum L. r. latifolium hutch) cycle in the State of Goiás, Brazil, by applying the method of growing degree-days (GD), and considering, simultaneously, its time-space variation. The model was developed as a linear combination of elevation, latitude, longitude, and Fourier series of time variation. The model parameters were adjusted by using multiple-linear regression to the observed GD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Some models provided theoretical insights that can contribute to the improvement of water use efficiency in cotton cultivation and the identification of optimal application rates of soil conditions necessary for the development and productivity of plants (Su, Wang & Shan 2015). A mathematical model was developed and validated to estimate the duration of cotton cycle in the State of Goiás, Brazil (Antonini et al 2011). It was found that the models performed very well when they were compared with statistical models.…”
Section: Cotton Modelsmentioning
confidence: 99%
“…Some models provided theoretical insights that can contribute to the improvement of water use efficiency in cotton cultivation and the identification of optimal application rates of soil conditions necessary for the development and productivity of plants (Su, Wang & Shan 2015). A mathematical model was developed and validated to estimate the duration of cotton cycle in the State of Goiás, Brazil (Antonini et al 2011). It was found that the models performed very well when they were compared with statistical models.…”
Section: Cotton Modelsmentioning
confidence: 99%